Gruppe Akanthus Berlin. - Galerie an der Düssel, Düsseldorf (Düsseldorf : Galerie an der Düssel, 1978)
Arnoldi, Uz ; Breitling, Gisela ; Hübel, Peter ; Lüdcke, Joachim ; Müllerstaedt, Viktor ; Sillner, Manfred ; Turin, Ulrike
Ausstellung der Gruppe Akanthus Berlin, Galerie an der Düssel, Düsseldorf, 3.5. - 30.6.1978
boek